Mental Poverty and Economic Poverty in the District of Yurimaguas - Barboza-Zelada, Pedro Arturo; Freyre-Flores, Jerrica Oriana; Barboza- Vidarte, Junior Arturo; Rivera-Castaneda, Patricia Margarita; Ramos-Mendoza, Ivan; Cubas-Mori, Claude Ivy; Galleguillos-Madrid, Felipe Marcelo; Casanueva-Yanez, Galvarino (Journal of Posthumanism, 2025)
The main objective of this research is to analyze the internal and external factors that people have for the maintenance of poverty, because it is one of the problems within society that affects the population and this attracts other social problems. The study was basic, descriptive, correlational, non-experimental and cross-sectional in design. A survey was carried out on 300 residents, the results of which were that the level of mental poverty was average 45.67%. The level of economic poverty was average 49%. There is a direct and significant relationship between the dimensions of economic poverty and mental poverty. The cognitive, behavioral, and emotional dimensions have a high positive correlation with the dimensions of economic poverty. It is concluded that there is a significantly direct relationship between economic poverty and mental poverty in the District of Yurimaguas, 2024. The significance was p = < 0.01. The correlation between both variables is positive, high Sp= 0.851. If mental poverty increases, economic poverty increases by 70.9%.